ANALISIS TITIK IMPAS PADA PENJUALAN KAMAR HOMESTAY TRI G DI KABUPATEN BERAU - MA'RIFAH YULIANI; DAWAMI BUCHORI; AIZA LATIFAH ADIWIYAH (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2022)
The purpose of this research is to find out the Break Event Point of selling room rental services at the Tri G Homestay in Berau Regency. The type of data in this research is quantitative data using secondary data obtained from Homestay Tri G in Berau Regency. Based on the results of the research, the break event point in 2019 reached Rp. 184,939,759,- or 627 rooms for a year, with sales of Exclusive rooms of Rp. 98,019,072,- as many as 280 rooms while sales of Superior rooms amounted to Rp. 86,921,921,- as many as 347 rooms.